Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan - Muhamad Zulfan Naufal Sugiarto; Cece Rakhmat; Arga Sutirsna (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect simultaneously or partially of leadership style variables and job satisfaction on employee productivity employees bordir company CV. Nuri Kota Tasikmalaya. The method of this research used the quantitative. The analysis method used multiple regression. Approach data collection in this research from the questionnaire to 43 respondens, and use measurement technique likert scale. The results of the analysis show that leadership style and job satisfaction simultaneously have a positive and significant effect on employee productivity. Partially the leadership style show a positive and significant effect on employee productivity. Partially the job satisfaction show a positive and significant effect on employee productivity.